Comparison of ventilation parameters and blood gas analysis in mechanically-ventilated children who received chest physiotherapy and suctioning vs. suctioning alone - Monalisa Elizabeth; Chairul Yoel; Muhammad Ali; M. Sjabroeddin Loebis; Hasanul Arifin; Pertin Sianturi (Indonesian Pediatric Society, 2016)
Background Chest physiotherapy and suctioning are routine methods for airway clearance in mechanically-ventilated children. However, chest physiotherapy has not been confirmed to affect ventilation parameters, such as tidal volume (TV), peak inflation pressure (PIP), peak inspiratory flow (PIF), and peak expiratory flow (PEF), as well as blood gas analysis (BGA) values in pediatric intensive care unit (PICU) patients.Objective To determine the efficacy of chest physiotherapy and suctioning vs. suctioning alone for improving the mechanical ventilation parameters and BGA.Methods This randomized, single-blind, clinical trial was conducted from November 2012 to June 2013 in the PICU at Haji Adam Malik Hospital, Medan. A total of 40 mechanically-ventilated pediatric patients were enrolled and divided into either the chest physiotherapy and suctioning group (24 subjects) or the suctioning alone group (16 subjects). Subjects underwent treatment, followed by monitoring of their ventilation parameters and blood gas analyses. Data were analyzed by independent t-test and Mann-Whitney test.Results Subjects comprised of 23 boys and 17 girls, with an age range of 1â€“204 months. After the respective treatments (chest physiotherapy and suctioning vs. suctioning alone), the ventilation parameters were as follows: median TV (60.0 vs. 56.5 mL, respectively; P=0.838), median PEF (10.4 vs. 10.8 I/s, respectively; P=0.838), median PIF (7.4 vs. 8.2 I/s, respectively; P=0.469), and mean PIP (17.3 vs. 15.6 cmH2O, respectively; P=0.23). The BGA values were: median pH (7.4 vs. 7.3, respectively; P=0.838), median pCO2 (38.4 vs. 36.2 mmHg, respectively; P=1.000), mean pO2 (136.6 vs. 139.2 mmHg, respectively; P=0.834), median HCO3 (20.4 vs. 22.7 mmol/L, respectively; P=0.594), median TCO2 (22.0 vs. 23.7 mmol/L, respectively; P=0.672), mean BE (-4.3 vs. -3.1 mmol/L, respectively; P=0.629), and median O2 saturation Â (98.5 vs. 98.3 %, respectively; P=0.967).Conclusion In mechanically-ventilated children in the PICU, ventilation parameters and BGA values are not significantly different between subjects who received both chest physiotherapy and suctioning and those who received suctioning alone.